Optical and electrical properties of Wurtzite copper indium sulfide nanoflakes - Ho, John C. W. (2013)
Raman spectroscopic analysis and Hall measurement of wurtzite copper indium sulfide (CuInS2) were carried out. Nanocrystalline wurtzite CuInS2 (CIS) was synthesized by a solvothermal reaction route for these studies. It is observed that the amount of sulfur source, time and temperature of the reaction are the key to control wurtzite phase formation of CuInS2. Wurtzite nanoflakes were formed at 150°C, with ethylenediamine as the selected solvent and the ratio of Cu:In:S precursor was kept at 1.1 : 1 : 5. The Hall measurement resulted in sheet resistivity, ρ, of ~2x105 Ω/sq, Hall coefficient of ~10 m2/C, mobility of ~0.5 cm2/V-s and hole concentration of ~7×1013 /cm2. Slight shift in the Raman spectra of 1-2 cm-1 was observed between wurtzite and roquesite CuInS2 and was attributed to the stoichiometric variation in Cu/In and/or changes in the chemical environments of the two crystal structures.